Sistem Pembagian Harta Waris di Indonesia berdasarkan Hukum Islam dan Hukum Adat - Hidayat, Rahmat; Maulina, Nia; Wiranti; Irwansyah, Wawan; Abadi, Lukman Tri Jaya (AL-SULTHANIYAH, 2025)
Indonesia, as a country that embraces legal pluralism, possesses diverse systems in the distribution of inheritance, namely Islamic inheritance law and customary inheritance law. This study aims to comparatively analyze the principles and mechanisms of inheritance distribution based on both systems using a normative juridical approach and descriptive-qualitative analysis method. The findings show that Islamic inheritance law is codified and normative, with fixed shares determined by syar’i sources such as the Qur’an and Hadith. In contrast, customary inheritance law is flexible and contextual, adjusted to social structures and kinship systems such as patrilineal (Batak), matrilineal (Minangkabau), and bilateral (Javanese, Buginese). The theory of legal pluralism is used to explain how Indonesian society integrates religious values, local customs, and communal justice in inheritance practices. The analysis also indicates that integrating these two legal systems can produce a more socially responsive model of inheritance distribution. This study recommends more explicit legal recognition of customary law within the national legal system and opens the possibility for a hybrid legal approach that accommodates substantive justice, deliberation (musyawarah), and public benefit (maslahah). Thus, legal pluralism should not be seen as a barrier to justice but rather as a foundation for reconstructing a more adaptive and contextual inheritance law system in Indonesia.